Produção científica sobre saúde indígena na biblioteca virtual em saúde Brasil (BVS): um estudo bibliométrico - Almeida, Natalia Rodrigues (Universidade Federal de São Carlos, 2021)
The history of indigenous population has been marked by tragic epidemics of infectious and parasitic diseases and in 2020, with the pandemic of COVID-19, the political, social and environmental vulnerability of these populations is even more evident. Therefore, it is considered essential to know the scientific production about these populations considered vulnerable due to their space and socio-cultural expropriation and how close it is to the priority needs of health care. This study is justified in the sense of contributing to identify knowledge producers in research on indigenous health, providing evidence of institutional centrality and the possibility of greater investment in research in indigenous health. The Science, Technology, Society field allows us to analyze aspects that provide this construction: who researches, what is researched and for whom it is researched. Thus, the research has as its general objective to map and quantify the scientific activity in Brazilian indigenous health through bibliometric methods considering the year of publication, journal, author and keywords. As for the methodological procedures, it is classified as descriptive with a quantitative approach. The informational source chosen for the research was the Virtual Health Library Brazil, which is an integral part of the Virtual Health Library for Latin America and the Caribbean and to assist in the organization of the data, the StArt tool was used. From the search strings used in the VHL Brazil portal, 1083 articles were identified; after reading the articles and predefined inclusion and exclusion criteria, 126 articles were kept for analysis purposes. For the discussion of articles from the perspective of Science, Technology and Society, it was considered important to indicate: indigenous cultural issues on each theme; change in habits and aspects related to technologies. The year indicator showed considerable growth only in 2014, with more periods of stability than growth or retraction of publications. The periodical indicator presented the Public Health Notebook with the largest number of publications. Regarding the author indicator, the one that most published in the analyzed period was Santos, Ricardo Ventura. And from the indicator of the keywords of the articles, it was possible to find out which themes were most addressed in the period from 2010 to 2018 and they are: oral health, followed by women's health, tuberculosis, nursing and surveillance and nutritional status. As a limitation of the research, in order to better understand the scientific progress in relation to the recovered targeted subjects through the StArt tool research, it should be pointed out the need for an analysis of the articles in relation to the methodological issues; it would also be interesting to expand the study to books, theses and dissertations and scientific events. In addition, it was observed that the theme of women's health has 4 lines of research in the Research Priority Agenda of the Ministry of Health, which would be a specific theme to be studied in new research.
Scientific production on indigenous health in the Virtual Health Library Brazil (VHL): a bibliometric study
Keywords: Saúde indígena; Bibliometria; Ciência Tecnologia e Sociedade; Indigenous health; Bibliometrics; Science, Technology and Society; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::METODOS QUANTITATIVOS. BIBLIOMETRIA